Efficacy of 5 and 10 mg donepezil in improving cognitive function in patients with dementia: a systematic review and meta-analysis - Sheikh, Mehak; Ammar, Mohammad (Frontiers in Neuroscience, 2024)
Objective The purpose of this study was to compare donepezil at 5 mg and 10 mg/day against a placebo to systematically evaluate its effectiveness in improving cognitive function among patients suffering from dementia at any stage. Method For this systematic review and meta-analysis, we looked up Medline, Scopus, Embase, Web of Science, and The Cochrane Library for articles on the efficacy of donepezil in dementia published in the past 20 years and summarized the placebo and intervention data. Initially, a total of 2,272 articles were extracted using our search query and after the inclusion and exclusion criteria set for extraction of data, 18 studies were included in this review using PRISMA flowchart. The ADAS-cog and MMSE assessment scales were used for measuring the outcomes using IBM SPSS 29.0 for the meta-analysis. Result The meta-analysis comprised a total of 18 RCTs (randomized controlled trials) that were randomized to receive either donepezil 5 mg/day (n = 1,556), 10 mg/day (n = 2050) or placebo (n = 2,342). Meta-analysis concerning efficacy showed that donepezil at 10 mg/day significantly improved the MMSE score (g: 2.27, 95%CI: 1.25–3.29) but could not substantially reduce the ADAS-cog. At 5 mg/day donepezil, an overall slight improvement in MMSE score (Hedges’ g: 2.09, 95%CI: 0.88–3.30) was observed. Conclusion Both donepezil 5 mg/day and 10 mg/day doses demonstrated improved cognitive functions for patients with dementia, however results indicated that the 10 mg/day dose was more efficacious.